THE ROLE OF LAW KNOWLEDGE IN BUSINESS DEVELOPMENT (IN CASE OF LEGAL SUPPORT) - Umaraliyev Zulfiqor Xaydaraliyevich; Gulnara Shermatova (Scholar Express Journals, 2022)
Timely legal assistance contributes to the successful functioning of the business. One of the ways to get it: subscription service, legal background, support of a professional in the field of law, are able to create a reputation as a reliable partner and minimize the risks of entrepreneurial activity.
Keywords: Law development; legal services; legal support